2017
DOI: 10.3389/fmicb.2017.01999
|View full text |Cite
|
Sign up to set email alerts
|

Caprylic and Polygalacturonic Acid Combinations for Eradication of Microbial Organisms Embedded in Biofilm

Abstract: There is a need for non-antibiotic, antimicrobial compositions with low toxicity capable of broad-spectrum eradication of pathogenic biofilms in food preparation and healthcare settings. In this study we demonstrated complete biofilm eradication within 60 min with synergistic combinations of caprylic and polygalacturonic (PG) acids in an in vitro biofilm eradication model against representative hospital and foodborne infectious pathogen biofilms (methicillin-resistant Staphylococcus aureus, multidrug-resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
1
17
1
Order By: Relevance
“…[22] Of the respective acid, aldehyde and alcohol, the fatty acid is the most tolerated compound. [23] However, relatively low concentrations of aliphatic acids and derivatives cause growth inhibition, cell membrane perforation and leakage, thus disrupting the electron transport chain, uncoupling oxidative phosphorylation and ultimately diminish ATP production. [24] A concentration of 30 mM octanoic acid, e. g., caused 46 % of increased leakage of ions in E. coli K-12 MG1655 cell membranes.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Of the respective acid, aldehyde and alcohol, the fatty acid is the most tolerated compound. [23] However, relatively low concentrations of aliphatic acids and derivatives cause growth inhibition, cell membrane perforation and leakage, thus disrupting the electron transport chain, uncoupling oxidative phosphorylation and ultimately diminish ATP production. [24] A concentration of 30 mM octanoic acid, e. g., caused 46 % of increased leakage of ions in E. coli K-12 MG1655 cell membranes.…”
Section: Introductionmentioning
confidence: 99%
“…is might be the primary reason for the difference in time to fully colonize the catheter shaft; in the case of the model, it took one day whereas in the physiologic system it typically takes at least an extra day [17]. e PG + CAP antimicrobial combination was previously shown to be effective in eradicating biofilms of a wide range of organisms [9]. We also demonstrated that it had very low cytotoxicity towards human fibroblasts.…”
Section: Discussionmentioning
confidence: 70%
“…Caprylic acid is a naturally occurring fatty acid present in significant quantities in breast milk, coconut oil, and other natural fluids. It has been designated generally regarded as safe by regulatory agencies and has been safely used in intravenous parenteral nutrition formulations, as a dietary supplement, and topically for skin, hair, and wound care [9,18]. Polygalacturonic acid is naturally derived from pectin and typically isolated from citrus rind of apple pomace [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations